Pengaruh Massa Pasir Silika terhadap Penurunan Konsentrasi Fe pada Sistem Penjernihan Air - Nadia Natalia Simamora; Suparno Suparno (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of silica sand mass in the air purification system on the decrease in Fe concentration. The type of research used is experimental research. The water purification media used in the research were silica sand and gravel. The mass of gravel used in the water purification system is constant, namely 500 grams. The mass of silica sand used varies, namely 200 grams, 400 grams, 600 grams, 800 grams and 1000 grams. The research was carried out through three stages, namely the stages of preparation, implementation, and data collection. The effect of the mass of silica sand in the air purification system on decreasing the concentration of Fe showed positive results. The results of research with a fixed mass of gravel and varying masses of silica sand showed a decrease in Fe concentration after water purification with a value that met environmental health quality standards and water health requirements Fe (iron) content below 1 mg/L or ppm so that the water worth using.